2014
DOI: 10.1590/2317-1545v36n4997
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and physiological quality of seeds with burn down herbicides at the pre harvest of bean crops

Abstract: -The physiological quality of bean seeds is influenced by the production environment and management practices employed during cultivation. The objective of this study was to evaluate the productivity and physiological quality of bean seeds after desiccant applications at different times at pre-harvest. A randomized block design was used, with a factorial (3x3) + 1 arrangement, where the application of three desiccants was tested: glyphosate (960 g a.i. ha -1 ), paraquat dichloride (240 g a.i. ha -1 ) and glufo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…For SMoC calculation, seed Mo concentration in μg g -1 was multiplied by the average mass of one dry seed (in g). Seed quality was evaluated by standard germination and accelerated aging tests according to methodology described by Pinto, Basso, Kulczynski, and Bellé (2014). In these two tests, a randomized complete block design with four replications was used.…”
Section: Methodsmentioning
confidence: 99%
“…For SMoC calculation, seed Mo concentration in μg g -1 was multiplied by the average mass of one dry seed (in g). Seed quality was evaluated by standard germination and accelerated aging tests according to methodology described by Pinto, Basso, Kulczynski, and Bellé (2014). In these two tests, a randomized complete block design with four replications was used.…”
Section: Methodsmentioning
confidence: 99%
“…Lamego et al (2013), in studies with soybean seeds, also noticed a reduction in germination percentage in later desiccations. Pinto et al (2014) found a smaller amount of normal seedlings in the germination test when using the herbicide ammonio-glufosinate for bean desiccation. Domingos et al (1997) observed reduction in germination and vigor when this same herbicide was applied to carioca bean seeds with water content between 37% and 42%, using the dose of 400 g ha -1 .…”
Section: Resultsmentioning
confidence: 92%
“…There was no difference in the application of ammonium-glufosinate in relation to the additional (harvested with 18% water) at 50%, 75% and 100% doses compared to the recommended average dose of this herbicide (1.9 L ha -1 ), regardless of the time of application (Table 3). Pinto et al (2014) observed that ammonium-glufosinate reduces the number of normal bean seedlings, compared to the control treatment (without desiccant application, harvested together with the other treatments), for all application times. Tavares et al (2015) found a linear reduction in the percentage of normal bean seedlings in the first count, with increasing doses of the herbicide saflufenacil, in the evaluations performed after harvest, corroborating the results of the present study.…”
Section: (A) (B) (C)mentioning
confidence: 82%
See 1 more Smart Citation
“…These results corroborate with those found with Marcandalli (2011) when observing that glyphosate negatively influenced the physiological quality of soybean seeds. There were fewer normal seedlings in the germination test when the ammonium glufosinate was used in the bean crop (Pinto et al 2014 2014), where the minimum germination required for the marketing of canola seeds is 80%. With the exception of the additional control in the second season of application, which germinated 94%, all other treatments, in both seasons, obtained inferior results.…”
Section: IIImentioning
confidence: 99%